Pendekatan Etnofarmasi Tumbuhan Obat Imunomodulator Suku Tengger Desa Ngadas, Kabupaten Malang, Indonesia - Bhagawan, Weka Sidha; Aziz, Yaya Sulthon; Teguh Pamungkas, Rizki Putra (Journal of Islamic Medicine, 2020)
Background: Ethnopharmaceutical is an approach that is emphasized to explore and inventory the local knowledge of an ethnic community or group about the use of a substance for treatment. The Tengger tribe is one of the tribes in Indonesia that still maintains knowledge of medicine from their ancestors.This study documents medicinal plant species and traditional knowledge related to the immunomodulators of the Tengger tribe who inhabit Ngadas village in TNBTS, Indonesia.Methods: This study uses the Snowball Sampling method which begins with the determination of the key sample with purposive sampling. Furthermore, the data were analyzed by UV, ICF, and FL.Results: This study documented 21 types of traditional medicinal plants belonging to 18 families used to treat 8 types of diseases of the human immune system. The data collection on the 10 selected immunomodulatory medicinal plants showed that the leaves, decoction, and oral use were the highest yields.Conclusion: Use Value, Informant Consensus Factor, and Fidelity Level value of recorded immunomodulatory medicinal plant species will provide a phytochemical basis reference in the discovery of new active compounds in the future and conservation practices In this regard, it is necessary to pay attention to the conservation of traditional medicinal plants and indigenous knowledge related to medicine in the Tengger tribe of Ngadas Village to preserve them in the future.